Composition equivalents of stainless steels understood via gamma stabilizing efficiency - Shuqi Zhang (Nature Portfolio, 2021)
Abstract The phase-type of a stainless steel is generally predicted by equivalent equations in terms of a major austenitic (γ) or ferritic (α) stabilizer Ni or Cr. The present paper attempts to understand the equivalent methods in stainless steels via the slopes of the phase boundary lines separating γ and γ + α phase zones. The prevailing equivalent coefficients are well interpreted using the slope ratios of the alloying elements divided by that of Ni or Cr, after analyzing over one hundred common stainless steels. Different from traditional composition equivalents which evaluate γ stabilizers and α stabilizers separately; the new equivalent scheme provides a unified phase stabilizing parameter for all alloying elements in stainless steels. This parameter is defined as γ stabilizing efficiency. Its negative or positive sign indicates γ stabilizer or α stabilizer, and its value represents the stabilizing efficiency.